Structural evolution during a surge in the Paulabreen glacier system, Svalbard. Issue 273 (14th February 2023) - Lovell, Harold; Fleming, Edward J.
Abstract: We assess the evolution of glaciological structures during the 2003–05 surge in the Paulabreen glacier system, Svalbard. Glaciological structures on the glacier surface were mapped using aerial photographs captured in the early stages of the surge (2003) and 5 years after surge termination (2011). Three-dimensional measurements of glaciological structures were collected at the tidewater front in 2013. These datasets document the physical changes during (1) the late quiescent phase; (2) the early phase of the surge as the surge front propagated down Skobreen and advanced into Paulabreen and (3) the final stages of the surge following the surge front reaching the glacier terminus. Crevasse patterns and clusters of arcuate shear planes record zones of compressive and extensional flow associated with the downglacier progression of the surge front. The transfer of surging ice from Skobreen into Paulabreen caused lateral displacement of the medial moraines to the northeast. At the ice front, this movement tilted glaciological structures in the same direction. Structures at the southwest margin record strike–slip faulting and the elevation of debris into the ice in a zone of compression and transpression. We summarise these observations in a schematic reconstruction of structural evolution during the surge.